Modern instruments of state regulation in the field of support of renewable energy sources - Bolyssov, T.K. (BUKETOV BUSINESS REVIEW, 2019)
In the article the role of instruments (preferential tariffs, standards, loans, grants, etc.) used for state support of renewable energy development is discussed. The author analyzes the controversial aspects of the classification of renewable energy support tools in terms of financial and institutional impact on supply and demand, which are based on price, cost and volume. In the Republic of Kazakhstan, according to the author, various instruments of state regulation are used for the development of renewable energy sources: target indicators of development, fixed tariffs, auctions, targeted assistance, training, research, technical regulation and legal regulation. The article focuses on the renewable energy market worldwide, where financial and non-financial instruments are used to stimulate the usage of renewable energy sources. The article highlights that common financial support tools include investment subsidies, credit subsidies, reduced interest rates, tax breaks or tax exemptions and government spending on research. According to the author, non-financial instruments stimulate the development of renewable energy sources by improving the necessary infrastructure to simplify market entry. Specific recommendations on the use of instruments of state support of renewable energy sources are given by the author taking into account international experience.